PENGARUH RASIO KEUANGAN, DAN KEPUTUSAN INVESTASI TERHADAP NILAI PERUSAHAAN DENGAN KEBIJAKAN DIVIDEN SEBAGAI PEMODERASI - Ni Putu Yuria Mendra; I Gede Cahyadi Putra; Putu Cahya Putri (KRISNA: Kumpulan Riset Akuntansi, 2026)
Firm value is an important indicator for investors as it reflects market confidence and corporate performance. However, prior studies show inconsistent results regarding the effects of profitability, liquidity, and investment decisions on firm value, particularly when dividend policy is considered. This study aims to examine the influence of profitability, liquidity, and investment decisions on firm value with dividend policy as a moderating variable. The research employs a quantitative approach using secondary data from banking companies listed on the Indonesia Stock Exchange during 2022–2024. Data were analyzed using Moderated Regression Analysis (MRA). The results indicate that profitability and investment decisions have a positive effect on firm value, while liquidity has no significant effect. Dividend policy does not moderate the relationship between profitability and liquidity with firm value, but it strengthens the effect of investment decisions on firm value. These findings suggest that investors place greater emphasis on long-term growth prospects reflected in investment decisions, particularly when supported by dividend policy. Further researchers are advised to consider cash flow-based liquidity measures, such as Cash Flow from Operations (CFO) or Cash Ratio, and dividend policy moderating variables that reflect investors' long-term orientation, such as Dividend Yield, Dividend Stability, or Free Cash Flow (FCF), so that research results are more relevant in assessing company value and future growth prospects.